Network topography and default contagion in China's financial system - Jens Fittje; Helmut Wagner (ZBW - Leibniz Information Centre for Economics, 2020)
The topography of China's financial network is unique. Is it also uniquely robust to contagion? We explore this question using network theory. We find that networks that are more concentrated are less fragile when connectivity is low. However, they remain vulnerable to the occurrence of large-scale default cascades at higher levels of connectivity than a decentralized network. We implement Chinese characteristics into our model and simulate it numerically. The simulations show, that the large state-controlled banks act as effective stopgaps for contagion, which makes the Chinese network relatively robust. This robustness persists even when a medium sized bank defaults.
Keywords: E44; 330; Interbank Network; Financial Contagion; China's interbank market; Financial market stability; Complex networks; Network topography